2011
DOI: 10.4028/www.scientific.net/amr.396-398.52
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Antioxidant Activities of Total Alkaloids from the Fruits of <i>Evodia rutaecarpa</i> <i>(Juss.)</i> Benth

Abstract: The total alkaloids (TAE) were obtained from the fruits of Evodia rutaecarpa (Juss.) Benth. The antioxidant activities of TAE towards the inhibitory effect on 2, 2’-diphenyl-1-picrylhydrazyl (DPPH) free radical, total antioxidant capacity, and inhibition on lipid peroxidation were investigated. TAE was found that the total antioxidant capacity and inhibitory lipid peroxidation are superior to synthetic antioxidant 2, 6-di-ter-butyl-4-methylphenol (BHT), but scavenging activity on DPPH radical is lower than tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
(4 reference statements)
0
4
0
Order By: Relevance
“…In the present study, 15 weeks of JKW administration significantly reduced lipid peroxidation and triglyceride and cholesterol accumulations in mice liver. The antioxidant activities of S. baicalensis and E. rutaecarpa [28, 37] might also contribute to the observed effects of JKW. In addition, JKW supplementation reduced hepatic damage caused by lipid accumulation and enhanced the activities of the liver enzymes GOT and GPT.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, 15 weeks of JKW administration significantly reduced lipid peroxidation and triglyceride and cholesterol accumulations in mice liver. The antioxidant activities of S. baicalensis and E. rutaecarpa [28, 37] might also contribute to the observed effects of JKW. In addition, JKW supplementation reduced hepatic damage caused by lipid accumulation and enhanced the activities of the liver enzymes GOT and GPT.…”
Section: Discussionmentioning
confidence: 99%
“…Benth has traditionally been used in Oriental medicine to treat headaches, gastrointestinal disorders, and amenorrhea for thousands of years (16,17). It has been reported that the extracts of E. rutaecarpa and its alkaloids exhibit anti-obesity, anti-dementia, antiinflammatory, and anti-oxidant effects (18,19). More recently, anti-cancer activities of E. rutaecarpa have been suggested.…”
Section: Discussionmentioning
confidence: 99%
“…E. rutaecarpa is commonly used as an analgesic, antiemetic, anti-inflammatory and astringent drug in TCMs (Tang and Eisenbrand, 1992). The total alkaloids obtained from the fruits of E. rutaecarpa was found and the total antioxidant capacity and inhibitory lipid peroxidation are superior to synthetic antioxidant 2, 6-di-ter-butyl-4-methylphenol (BHT), but scavenging activity on DPPH radical is lower than that of BHT at the same condition (Tan et al, 2011). Wang et al (2006) examined 25 TCMs that might be useful for antioxidant agents and pointed out that L. heterophyllus can effectively inhibit formation of •OH in a concentrationdependent manner.…”
Section: Samplesmentioning
confidence: 99%